Effects of Dim Light at Night on Food Intake and Body Mass in Developing Mice - Cissé, Yasmine M.; Peng, Juan; Nelson, Randy J. (Frontiers in Neuroscience, 2017)
Appropriately timed light is critical for circadian organization; exposure to dim light at night (dLAN) disrupts temporal organization of endogenous biological timing. Exposure to dLAN in adult mice is associated with elevated body mass and changes in metabolism putatively driven by voluntary changes in the time of food intake. We predicted that exposure of young mice to LAN could affect adult metabolic function. At 3 weeks (Experiment 1) or 5 weeks (Experiment 2) of age, mice were either maintained in standard light-dark (DARK) cycles or exposed to nightly dLAN (5 lux). In the first two experiments, food intake and locomotor activity were assessed after 4 weeks and a glucose tolerance test was administered after 6 weeks in experimental lighting conditions. In Experiment 3, tissues were collected around the clock at 6 hour intervals to investigate rhythmic hepatic clock gene expression in mice exposed to dLAN from 3 or 5 weeks of age. Male and female mice exposed to dLAN beginning at 3 weeks of age displayed similar growth rates and body mass to DARK-reared offspring, despite increasing day-time food intake. Exposure to dLAN beginning at 5 weeks of age increased body mass and daytime food intake in male, but not female, mice. Consistent with the body mass phenotype, clock gene expression was unaltered in the liver. In contrast to adults, dLAN exposure during the development of the peripheral circadian system has sex- and development-dependent effects on body mass gain.